Gastos deducibles en el Comercial Agrícola Jorgito del cantón Quinsaloma, periodo 2021. - Peralta Pincay, Kimberlyn Sulay (2023)
The agricultural sector is one of the most important in the Ecuadorian economy, and agricultural companies face multiple challenges to remain profitable, with expenses being a fundamental part of the equation. This case study focuses on Comercial Agrícola Jorgito and examines deductible expenses during the 2021 period to analyze their impact on the business's profitability and compliance with tax regulations. The COVID-19 pandemic and adverse weather conditions impacted the company's profitability, making it crucial to evaluate deductible expenses to understand their impact on the business's profitability. The objective of this research is to evaluate Comercial Agrícola Jorgito's deductible expenses during the 2021 fiscal period and analyze their impact on the business's profitability. The study highlights the severe consequences that the company can face if it fails to meet its tax obligations, such as fines and penalties from the relevant tax authorities. Therefore, it is crucial that deductible expenses are properly recorded to avoid errors in tax reporting and maximize the company's profitability. The research project uses a descriptive approach to evaluate the accounting of deductible expenses in a company and their impact on the tax due. A mixed research approach is employed, combining both quantitative and qualitative methods to obtain precise and reliable results.